Methods used in forecasting the development of the tourism services market (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
the article examines the methods used in forecasting the development of the tourism services market. A system of methods is used as an instrument in forecasting, with the help of which past trends of the enterprise are analyzed with the help of cause-and-effect parameters for the analysis of changes formed in the economic and social development potential of the firm.